Simulation model of water temperature variation in dual‐purpose canals considering return flow from upstream paddy fields. (3rd March 2022) - Kimura, Masaomi; Kobayashi, Satoru; Mitsuyasu, Marie; Xie, Wenpeng; Iida, Toshiaki
Abstract: High ambient air and water temperatures can cause high‐temperature damage to ripening rice grains after rice heading and has recently become a major issue of concern. Spill‐over irrigation (also referred to as continuous irrigation with running water) is an effective countermeasure that involves simultaneous irrigation and drainage to reduce the ponded water temperature in paddy fields. However, it is necessary to understand the impact of this technique on downstream water temperatures. In this study, the discharge and water temperature variations in a dual‐purpose canal (also referred to as irrigation‐cum‐drainage canal) were measured along the main canal of the Tedori‐gawa Shichika canal system in Japan. The discharge and water temperature variations in a branch drainage canal were also monitored to analyse the influence of the return flow on the water temperature in the main canal. Based on these observations, a new numerical model was developed to simulate the water temperature variations in the main canal considering meteorological conditions, heat transfer of water in the open canal, and return flow from upstream paddy fields. Finally, the model was applied to examine possible global warming scenarios and discuss the effectiveness of paddy water management in mitigating high‐temperature damage in downstream paddy fields. Résumé: Des températures ambiantes élevées de l'air et de l'eau peuvent causer des dommages à haute température à la maturation des grains de riz après l'épiaison du riz, et sont récemment devenues un sujet de préoccupation majeur. L'irrigation par débordement (également appelée irrigation continue avec de l'eau courante) est une contre‐mesure efficace qui implique une irrigation et un drainage simultanés pour réduire la température de l'eau des mares dans les rizières. Cependant, il est nécessaire de comprendre l'impact de cette technique sur les températures de l'eau en aval. Dans cette étude, les variations de débit et de température de l'eau dans un canal à double usage (également appelé canal d'irrigation et de drainage) ont été mesurées le long du canal principal du système de canaux Tedori‐gawa Shichika au Japon. Les variations de débit et de température de l'eau dans un canal de drainage secondaire ont également été suivies pour analyser l'influence du débit de retour sur la température de l'eau dans le canal principal. Sur la base de ces observations, un nouveau modèle numérique a été développé pour simuler les variations de température de l'eau dans le canal principal en tenant compte des conditions météorologiques, du transfert de chaleur de l'eau dans le canal ouvert et du flux de retour des rizières en amont. Enfin, le modèle a été appliqué pour examiner les scénarios possibles de réchauffement climatique et discuter de l'efficacité de la gestion de l'eau des rizières pour atténuer les dommages causés par les températures élevées dans les rizières en aval.